A FORMAÇÃO DE PRECEDENTES JUDICIAIS A PARTIR DA RECLAMAÇÃO CONSTITUCIONAL NO ÂMBITO DO DIREITO PROCESSUAL DO TRABALHO - Stefanelli, Daniella Goncalves (2022)
Although Law no. 13.015, of July 21th, 2014 that deals with the appeals within the scope of the Labor Court, with one of its many purposes being the achievement of uniform decisionmaking had already introduced binding precedents in the Consolidation of Labor Laws, it was the advent of the Civil Procedure Code of 2015, applied in a subsidiary and supplementary way to other branches of procedure law, that consolidated the implementation of the system of judicial precedents in Brazil. In order to give viability and effectiveness to the aforementioned system, old legal instruments underwent severe remodeling, such as the constitutional complaint that had its hypotheses expanded for the application of legal theses arising from some statements, decisions and judgments that, as a matter of option of the infraconstitucional legislator reflected in Article 927 of the Civil Procedure Code, which is the subject of controversy regarding its taxation , conform binding judicial precedents, factor that allows questioning the constitutionality of such expansion, based on the original functions of the legal instrument. The theme acquires relevant contours when, given the flexible stability of judicial precedents, there is the possibility of its modification and its overruling, which currently has in labor procedural law more specific and better designed mechanisms of these purposes, notwithstanding the judgment of the Incidental Motion for Unconstitutionality no. 696-25.2012.5.05.0463 by the Full Court of the Superior Labor Court declared the unconstitutionality of Article 702, item I, “f”, § 3°, of te Consolidation of Labor Laws. Rare constitutional or legal provisions deals with the modification and overruling of judicial precedents, which procedure is allocated in the internal regulations of the national courts, with emphasis on the Internal Regulation of the Superior Labor Court, raising discussions about the limits of the normative power of the courts. It is in this context that the present research will be dedicated to ascertaining if and when the judicial provisions resulting from the judgment of constitutional complaint, which is not included in the list of the Article 927 of the Civil Procedure Code, nor in the list of the Article 15 of Normative Instruction no. 39, edited by Resolution no. 203, of March 15th, 2016, of the Superior Labor Court, can form judicial precedents, notably in the scope of procedure labor law, with a focus on the Superior Labor Court, defining the nature attributed to them. Affiliated to the critical-methodological line and the legal dogmatic aspect, this study will be developed by surveying and analyzing constitutional, legal and regimental provisions (primary data) and specialized bibliographies (secondary data) relating to judicial precedents and constitutional complaint in the areas of procedure law most relevant to the subject, simultaneously with the examination of the several judicial provisions (documentary support material) rendered in their vast majority by the Federal Supreme Court, selected based on the relevance that is already attributed to them by the doctrine and obtained through researches in jurisprudence and precedent search tools on the websites of the aforementioned courts, allowing the verification of the hypothesis and the solution of the present study.